HELMINTHIASIS IN ALPACAS (Vicugna pacos) OF TWO PEASANT COMMUNITIES IN MACUSANI, PUNO DURINGTHE DRY SEASON - Contreras S., Nancy (2014)
The study aimed to estimate the prevalence of gastrointestinal helminth in alpacas oftwo peasant communities in Macusani district, Puno, Peru during the dry season and itsassociation with age and origin; also, to establish the average parasite burden and to identify the genus of helminth presents. Stool samples were collected from 1319 alpacasfrom August to October 2010 and were processed by the flotation method using Willissolution and by the spontaneous sedimentation technique. The parasite burden andidentification of nematode larvae was done by the McMaster method and the modifiedBaermann technique respectively. The prevalence of helminths was 63.9 ± 2.6%. Thelogistic regression test showed that age was a risk factor for the presence of helminths(p3 years old, while there wasno difference in the prevalence between the two communities. The parasite burden pereach genus was lower than 100 epg. Helminth genus identified were Nematodirus,Trichuris, Moniezia, Cooperia, Oesophagostomum, Trichostrongylus, Ostertagia,Bunostomum, Haemonchus, Capillaria and Lamanema, where the prevalence ofNematodirus spp was the highest (52.8%) followed by Trichuris spp (10.8%) and Monieziaspp (9.6%).